Level of Affordability and Comfort for Middle-Class People (Case Study of Residents of Menara Rungkut Apartment, Surabaya) - Joko Santoso; lntan Kusumaningayu; Fanesa Dwi Retno Aprilia Sanjaya; Devita Asmara Wadani (International Conference of Innovation and Community Engagement, 2025)
Currently, the ability to fulfill the community's need for housing is very limited, and this is due to the decreasing supply of land. To fulfill this gap, the private sector has also attempted to meet housing needs in the form of apartments. Apartment numbers have grown rapidly. However, in terms of pricing, it can be said to be fairly expensive, particularly for middle-class people. Apartment, with the smallest type being a studio (22 m2), making it affordable to middle-class people. However, this condition also raises concerns about residents' comfort, especially as the number of family members increases. If one wants to buy another apartment unit, price is also a consideration. This study aimed to determine the level of affordability and comfort for middle-class people. The method used was descriptive-quantitative with primary data collection by conducting surveys with the residents and gathering reports provided by management. The findings revealed that in comparison to Maslow's Hierarchy of Needs, the needs of residents in Menara Rungkut Apartment that are met are physiological, security in having a place to stay, and a little social fulfillment. In terms of affordability, they chose Menara Rungkut Apartment because of its low price and proximity to the office. Meanwhile, in terms of comfort, residents feel quite comfortable because of its safe, fairly clean, quiet, and easily accessible public facilities. However, it is still expected that the management can improve building maintenance so that it becomes a more comfortable environment for residents, particularly middle-class residents.